Análisis del sector industrial de transporte de alimentos usando tecnología en aplicaciones de delívery - Zavaleta Cavero, Daniel Alejandro (2021)
The sector which will be analyzed in this paper will be that of food transport using delivery platforms in the Peruvian market using 2020 as the year of study, at which time the covid-19 pandemic broke out in the world. This market niche is made up of the union of 3 other sectors, that of food, transport, and technology; since the service that was offered from the beginning was to mobilize food orders, using only the cell phone in an application. This same is mainly composed of 3 companies, which represent approximately 68% of total sales; These companies are Glovo, of Spanish origin, Rappi, of Colombia, and Uber Eats, of the United States, with shares of approximately 48%, 13% and 7% respectively; contributing with the movement of 800 million soles in the economy and creating 8000 jobs. However, due to the context of the pandemic, the niche companies were forced to work with new restrictions, of which the political and economic were the most difficult, despite the circumstances, the sector proposes to achieve a 21% rebound compared to 2019 in a post-pandemic scenario, benefiting from the avoidance of agglomerations in the markets, but slowly due to mistrust. Niche companies have found themselves making investments since previous years, such as the creation of SuperApps, increasing offers per order, and other actions that would contribute to the recovery.